2018
DOI: 10.1038/s41598-018-28978-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for quantitative real-time PCR in tiger beetles across sexes, body parts, sexual maturity and immune challenge

Abstract: Reference genes are frequently used as normalizers for expression studies despite not being previously verified to present suitable stabilities. Considering the interest that tiger beetles have generated in the past years, resulting in a variety of studies, it is crucial to dispose of a validated reference gene panel for expression studies. Nine candidate genes were tested in Cicindela campestris and Calomera littoralis across several conditions and their transcription levels were assessed with geNorm, NormFin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Hence, this is the first report for suitable reference genes in any Ips bark beetles. Accurate normalization using a stable reference gene is necessary to conduct gene expression studies under specific experimental conditions and to avoid erroneous differences in target gene expression (Andersen et al, 2004;Bustin et al, 2005;Ferguson et al, 2010;Cheng et al, 2013;García-Reina et al, 2018;Xie et al, 2021). The results obtained in this study indicate that the stability of reference genes in ISx can differ under various experimental conditions, including developmental stage, sex, and tissue-specific conditions, and exposure to abiotic conditions (Tables 2-5 and Figures 1B-4) as observed in other reference gene finding studies in insects (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, this is the first report for suitable reference genes in any Ips bark beetles. Accurate normalization using a stable reference gene is necessary to conduct gene expression studies under specific experimental conditions and to avoid erroneous differences in target gene expression (Andersen et al, 2004;Bustin et al, 2005;Ferguson et al, 2010;Cheng et al, 2013;García-Reina et al, 2018;Xie et al, 2021). The results obtained in this study indicate that the stability of reference genes in ISx can differ under various experimental conditions, including developmental stage, sex, and tissue-specific conditions, and exposure to abiotic conditions (Tables 2-5 and Figures 1B-4) as observed in other reference gene finding studies in insects (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Vacuolar-type ATPase ( V-ATPase-A ) is a proton translocating pump responsible for ATP hydrolysis, one of the most highly conserved eukaryotic proteins. The V-ATPase-A gene had been commonly used as a reference gene in Amrasca biguttula for experiments involving starvation stress and different life stages (Singh et al, 2018 ); for sex-specific experiments in Cicindela campestris (García-Reina et al, 2018 ). On the contrary, V-ATPase-A gene expression was highly unstable in the developmental and tissue stages of Mythimna separata (Li et al, 2018c ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its publication in 2018, this article by Shakeel and colleagues on insects has been cited 22 times by articles in PubMed. Fourteen of these citing articles are those evaluating candidate reference genes [ 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. We hope that our critical review will similarly stimulate future research on experimentally validating reference genes for gene expression studies in Aspergillus (and in fungi in general) using RT-qPCR.…”
Section: Concluding Remarks and Recommendationsmentioning
confidence: 99%
“…It is pretty clear now that a single reference gene is not appropriate for the more comprehensive experimental conditions, and it can generate an error in the gene expression estimations causing nonoptimal interpretation of the data 25 , 34 , 35 . For mitigation, it is often recommended to use multiple reference genes to minimize variations by RT-qPCR normalization 23 , 36 , 37 . Several research studies revealed that most reference gene expression depends on samples/experimental conditions, suggesting no universal reference gene is available for all experimental conditions 38 .…”
Section: Introductionmentioning
confidence: 99%